2012
DOI: 10.1242/dev.078675
|View full text |Cite
|
Sign up to set email alerts
|

The protein kinase MLTK regulates chondrogenesis by inducing the transcription factor Sox6

Abstract: SUMMARYSox9 acts together with Sox5 or Sox6 as a master regulator for chondrogenesis; however, the inter-relationship among these transcription factors remains unclear. Here, we show that the protein kinase MLTK plays an essential role in the onset of chondrogenesis through triggering the induction of Sox6 expression by Sox9. We find that knockdown of MLTK in Xenopus embryos results in drastic loss of craniofacial cartilages without defects in neural crest development. We also find that Sox6 is specifically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Distinct from many NC regulatory factors, ectodermal expression of Sox5 is initially broad and low at early NC stages before becoming strongly enriched at the neural plate border (NPB) (Suzuki et al, 2012, Figure S1A-F). It is also maternally provided and expressed throughout the ectoderm at blastula stages (Figure S1G,H).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Distinct from many NC regulatory factors, ectodermal expression of Sox5 is initially broad and low at early NC stages before becoming strongly enriched at the neural plate border (NPB) (Suzuki et al, 2012, Figure S1A-F). It is also maternally provided and expressed throughout the ectoderm at blastula stages (Figure S1G,H).…”
Section: Resultsmentioning
confidence: 99%
“…NC cells maintain expression of Sox5 as they begin to migrate, similar to what has been described in chick (Morales et al, 2007; Perez-Alcala et al, 2004). The closely related SoxD factor, Sox6, was not detected in early NC cells (Suzuki et al, 2012, Figure S1I). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No role had been assigned to ZAK in vertebrate limb development, but knockdown of its Xenopus laevis ortholog mltk was previously shown to result in loss of craniofacial cartilage (Gotoh et al 2001;Suzuki et al 2012). ZAK was shown to be a direct target of TP63 binding, and a functional link of both proteins was suggested; ZAK has also been shown to suppress the JNK pathway (Yang et al 2006;Wang et al 2014a).…”
Section: Identification Of Zak Mutations In Split-foot Malformation Wmentioning
confidence: 99%
“…6 ZAKα plays a kinase role, and it has been demonstrated that ZAKα can phosphorylate histone 3 at Ser 28 . 9 These studies have led many scientists to believe that ZAKα may play an oncogenic role in promoting tumour development. 8 ZAKα can also regulate chondrogenesis by inducing the transcription factor Sox6.…”
mentioning
confidence: 99%